Study of physiochemical properties of trisubstituted pyrazole derivatives using polar aprotic solvents - Poonam Devi; Hardeep Anand; Rashmi Pundeer; Suresh Kumar (Scientific Reports)
Abstract Pyrazole derivatives are aromatic heterocyclic compounds endowed with multifaceted applications. In the present study 1,3,4-trisubstituted pyrazoles derivatives have been synthesized for the purpose of studying their physical properties and their characterization was done by FTIR, 1H NMR and 13C NMR spectroscopic technique. The measurement of densities (ρ) and viscosities (η) of solutions of substituted pyrazole derivative in polar aprotic solvent i.e., Dimethyl sulfoxide (DMSO), nitromethane (NM) as well as in their 1:1 binary mixture (DMSO + NM) was done at 310 K over a wide range of solute concentration (5–100) × 10–4 mol dm−3. The experimental results were used to determine the excess molar volumes $$(V_{m}^{E})$$ ( V m E ) . The data of density–viscosity revealed the dipole–dipole interactions occurred between the pyrazole derivative (solute) and the solvent (DMSO, NM). Excess molar studies $$(V_{m}^{E})$$ ( V m E ) revealed that solute–solvent interaction was found to be stronger in case of nitromethane solvent.